Face-to-face versus 360° VR video: a comparative study of two teaching methods in nursing education - Abdulfatai Olamilekan Babaita; Mayumi Kako; Chie Teramoto; Miho Okamoto; Yoko Hayashi; Shinichiro Ohshimo; Takuma Sadamori; Minoru Hattori; Michiko Moriyama (BMC, 2024)
Abstract Background The practical sessions during skills laboratory simulation or clinical simulation are cores of nursing education. For this, different modalities have been devised to facilitate psychomotor skills learning. One of the commonly used educational material or instructional method to supplement skills learning across various disciplines is video-based teaching method. The opportunities of traditional two-dimensional video might be limitless and maximized with 360º virtual reality (VR) video, which offers immersive experience. This study incorporates 360º VR video into skills laboratory training as an alternative approach to face-to-face procedure demonstration. Methods An open-label, parallel (1:1), randomized controlled trial study was conducted among third-year undergraduate nursing students at Hiroshima University, Japan. The nursing students were block-randomized into 360º VR video and face-to-face demonstration group. After a 3-hour theoretical class of patient management on ventilator and closed-suction principles of mechanically ventilated patients in an Intensive Care Unit focused class, the 360º VR group watched the 360º VR video of closed tracheal suction (including oral) using the head-mounted display of Meta Quest 2 individually, while the face-to-face group attended the instructor's demonstration. A week after the skills laboratory, the students' psychomotor skills, knowledge, satisfaction, confidence were evaluated; the 360º VR video group's perception was explored; Wilcoxon rank-sum test was used to compare the two groups. Results A total of 57 students were analyzed; 27 students in the 360º VR video group and 30 students in face-to-face group. There were no statistically significant differences between both groups in skills, knowledge, and confidence. However, the face-to-face group had higher satisfaction level than the 360º VR group; this difference was statistically significant. In the 360º VR video group, 62% agreed that VR makes learning more interesting; more than half of students (62.5%) experienced VR sickness symptoms, and "feeling of drunk" is the highest. The students appreciated the ready to use, immersiveness, and realism; however, symptoms and discomfort, burdensomeness, and production limitations were improvements recommended. Conclusion Although face-to-face demonstration is the established method of teaching psychomotor skills to nursing students, the use of 360º VR video could achieve similar learning effect as an alternative approach.